Penilaian Fundamental dalam Pengambilan Keputusan Investasi pada Saham Pertambangan Batubara di Indonesia: Studi Komparatif pada Saham BUMI dan DEWA - Asnahwati Asnahwati; Maretta Selvana Siburian; Jeli Nata Liyas; Khansa Khalisah (Universitas Methodist Indonesia, 2026)
This study aims to analyze and compare the Price-to-Earnings Ratio (PER) and Price-to-Book Value (PBV) of PT Bumi Resources Tbk (BUMI) and PT Darma Henwa Tbk (DEWA) stocks to inform investment decision-making. A quantitative approach utilizing a comparative method was employed. The study population consisted of all market ratio data (PBV and PER) contained in the published financial statements of PT Bumi Resources Tbk (BUMI) and PT Darma Henwa Tbk (DEWA). The sample comprised PBV and PER data from the 2020–2024 period, selected via purposive sampling based on the criterion of data completeness throughout the observation period. Secondary data—specifically financial statements and stock prices from 2020 to 2024—were used. Data analysis techniques included descriptive analysis, normality testing, and difference testing using either the independent sample t-test or the Mann-Whitney U test. The results indicate a significant difference in PER between BUMI and DEWA stocks; BUMI exhibited a lower and relatively more stable PER. Conversely, no significant difference was found regarding PBV, with both stocks tending to be undervalued. These findings suggest that PER is more relevant than PBV for investment decision-making. The study implies that BUMI stock is better suited for a value investing strategy, whereas DEWA is more appropriate for a speculative strategy.